2015
DOI: 10.1016/j.ajodo.2015.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Bone and cartilage changes in rabbit mandibular condyles after 1 injection of botulinum toxin

Abstract: Introduction Temporary paralysis of the masseter muscle using botulinum toxin is a common treatment for temporomandibular disorders, bruxism, and muscle hypertrophy. Loss of masseter force is associated with decreased mandibular mineral density. Our objectives were (1) to establish whether bone loss at the mandibular condyle is regionally specific, and (2) to ascertain whether the treatment affects the condylar cartilage. Methods Young adult female rabbits received a unilateral masseter injection of botulinu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 30 publications
2
30
1
3
Order By: Relevance
“…According to animal studies using rodents, reduced masticatory muscle thickness resulting from BTX injections in the temporalis and/or masseter muscles could lead to changes in cortical and trabecular bone structures in masticatory load-bearing areas, the TMJ condyles and alveolar bones 17,21,23,24 . Other animal studies using rabbits showed similar results 16,18 . Most studies that investigated the relationship between BTX-induced masticatory muscle atrophy and mandibular bone loss were animal studies, and only a few human studies have performed a comprehensive analysis of bone quality and muscle thickness.…”
supporting
confidence: 63%
See 3 more Smart Citations
“…According to animal studies using rodents, reduced masticatory muscle thickness resulting from BTX injections in the temporalis and/or masseter muscles could lead to changes in cortical and trabecular bone structures in masticatory load-bearing areas, the TMJ condyles and alveolar bones 17,21,23,24 . Other animal studies using rabbits showed similar results 16,18 . Most studies that investigated the relationship between BTX-induced masticatory muscle atrophy and mandibular bone loss were animal studies, and only a few human studies have performed a comprehensive analysis of bone quality and muscle thickness.…”
supporting
confidence: 63%
“…Decreased masticatory muscle thickness also seemed to have direct effects on bone density of the ramus and coronoid process of the mandible [16][17][18]23,24 . Most studies about the association between BTX induced masticatory muscle atrophy and mandibular bone loss have been animal studies and sparse well-designed human studies have been carried out due to difficulties in analyzing craniofacial bone qualities in humans.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Accordingly, several studies have investigated the effect of BoNT-A injection on bony changes in adult animals 91011. Studies on adult rabbits have reported significant bony changes associated with muscle atrophy that lasted 12 weeks after the injection of BoNT-A 1011.…”
Section: Introductionmentioning
confidence: 99%